Implication of Industrialised Building System (IBS) : The Case of Trade Contractors in Malaysia - Theong, Maychuan; Abd Rashid, Rosli; Chai, Changsaar (International Journal of Engineering and Technology, 2018)
To further enhance the efficiency, capacity and capability of the Malaysian construction industry, the government has been aggressively championing the use of Industrialised Building System (IBS). However, several studies have pointed out that the trade contractors are very concern with the increasing use of IBS in the country because it will reduce their business opportunities.Â Therefore, the research is dedicated to address issues faced by the trade contractors with the adoption of IBS. The objectives of this paper are to uncover the impact of IBS to the trade contractors and to suggest solutions to address issues faced by the trade contractors with the implementation of IBS. A fundamental of the methodology is to adopt multiple case studies approach. These projects adopted both conventional and IBS construction method. A number of 8 projects were selected. Interview sessions are conducted with trade and main contractors. Collected data is then modelled by using the combination of fuzzy theory set and simple multi-attribute rating technique. Main contractorsâ€™ input on several success factors that lead to the penetration of trade contractors in IBS is evaluated. Some degree of involvement of trade contractors in IBS projects is recommended. It is significant for the trade contractors to obtain skills for IBS approach besides their existing crafts. Furthermore, the trade contractors are suggested to register themselves as IBS components installer as this does not involve high investment capital or they can join the other companies to increase their technical and financial capacity. These findings will inform on numerous policy initiatives to manage the business sustainability of the domestic trade contractors, to improve construction methods, then to modernise and upgrade the construction industry within the country.Â Â